State Essence in Conception by P. Lodiy - Y. M. Khodanych (Сибирское юридическое обозрение, 2014)
The article deals with the analysis of the main features of a state, such as unequal society, the society of free people, achievement of common security and prosperity as the goal of a state. The author offers the comparison of the concept of freedom in the doctrines offered by the great figures of the Enlightenment Epoch like J. J. Rousseau, C.-L. Montesquieu, J. Lock, T. Hobbes, P. A. Holbach, B. Spinoza.